Disputation by decree the public disputations between Reformed ministers and Dirck Volckertszoon Coornhert as instruments of religious policy during the Dutch Revolt (1577-1583) - Roobol, Marianne (Studies in medieval and Reformation traditions, 2010)
Summary: Prevailing scholarly analysis of the public disputations between D.V. Coornhert (1522-1590) and Dutch Reformed ministers is firmly rooted in a principled view of early modern tolerance. This study proposes a new point of departure, which involves breaking away from a Coornhert-centred reading of the debates in Leiden and the Hague, while focusing on the formal status of these disputations instead. Government support of the Reformed Church proved the backbone of these illuminating 'disputations by decree'. The public legitimization of the Reformed Church - a goal with both political and theological significance - was at stake. As a micro-history of two very unique occasions in Dutch history, this study sheds new light on the complex development of political and religious argument in the early phase of the Dutch Revolt.